An overview of activated carbon preparation from various precursors / Nur Deana Hasdi, Normadyzah Ahmad, Muhammad Khairil Ahya, Siti Wahidah Puasa - Hasdi, Nur Deana; Ahmad, Normadyzah; Ahya, Muhammad Khairil; Puasa, Siti Wahidah (Universiti Teknologi MARA Shah Alam, 2023)
Activated carbon plays an important role in the industry due to its uniqueness and special characteristics. Originally known as a good adsorbent, activated carbon has a very large surface area and high micro-porosity. Activated carbon has been widely used in petroleum, pharmaceutical, textiles and many other industries. Activated carbon can be derived directly from charcoal through chemical or physical activation. Nonetheless, activated carbon can also be obtained from other carbon precursors, such as biowaste (agricultural, municipal and industries) and natural resources (seed, leaves, fruits and barks). Generally, activated carbon can be derived from wastes through four steps; pre-processing of raw materials, thermal-conversion steps (pyrolysis or carbonization), activation, and modification. Both activation and modification were employed in the production of activated carbon to boost it’s absorption performance. These steps can be divided into chemical and physical steps that help alter the physical structure of activated carbon and modify the surface chemical properties of activated carbon. Due to its reliability as an adsorbent, activated carbon has been widely used to remove pollutants in wastewater treatment and the demand for activated carbon has been increasing every year. This article reviews methods for preparing activated carbon from various precursors and discussed their performances. This review article aimed to provide recent information on efforts made by various researchers in activated carbon preparation.